THE ROMANIAN ORGANIZATIONS AND THE PROJECT MANAGEMENT MATURITY - BELATRECHE, Mansour; BENHARRAT, Hayet; NISTOR, Razvan (Managerial Challenges of the Contemporary Society, 2017)
Nothing accommodates to the human life to accomplish and plan. Since the dawn of history, project has represented all the fascinated building, industries and infrastructures in the world. For this, in recent years, project management has shown great vitality in the field of management over the world due to its flexibility and feasibility. The current development of project management takes place in various professional and academic contexts and diversified through the multitude of interventions of professionals and researchers. The degree or extent of capability or competency regarding project management is referred to as "maturity. Due to the importance of the project management nowadays, this paper is meant to reveal these initiatives in this field, the different models, methods, techniques and tools usedfor this, and what is the Romanianorganization's capability or competency in managing projects?
Keywords: project management, models, techniques, tools; project management, models, techniques, tools and methods, project management maturity model, POR.